Integrating Ethnopedagogy and Local Wisdom into ESD-Based Curriculum: A Strategy for Strengthening Socio-Cultural Resilience in the Digital Era - Falaq, Yusuf; Sari, Mutiara Dwi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2026)
This study examines the integration of ethnopedagogy and local wisdom into an Education for Sustainable Development (ESD)-based curriculum as a strategy for strengthening socio-cultural resilience in the digital era. Employing a qualitative case study design, data were collected through interviews with 15 purposively selected informants (traditional leaders, parents, teachers, studio managers, and adolescents), participant observation, and documentation in three villages across the Mount Muria region, over a three-month period. Data analysis followed the interactive model of Miles, utilizing iterative cycles of data condensation, display, and conclusion drawing, supported by inductive coding to identify key themes. The findings suggest that local wisdom values in Guyang Cekathak, Wiwitan Kopi, and Kupatan traditions are internalized through ethnopedagogical practices, oral traditions, ritual ceremonies, and traditional arts and may foster students’ cultural identity, strengthen social cohesion, and increase adaptive capacity toward negative digital influences. The transformation of these values into an ESD-based curriculum, mapping traditions to SDGs and resilience indicators. This study a description of the currently unwritten annual tradition cycle can be adapted into formal school learning modules. The integration of these elements indicates a grassroots socio-cultural resilience mechanism that could, over time, contribute to broader national resilience. It offers a replicable model for culturally rooted ESD curriculum development elsewhere.